Nursery and grow-out culture of mangrove polychaete marphysa sp. - Caballero, Pedrita A.
Experiments on the polychaete Marphysa sp. Were conducted to determine the optimum stocking density in indoor nursery as well as optimum stocking density and culture period in outdoor grow-out ponds that can maximize polychaete biomass production. In the nursery experiment, early metatrocophores at four stocking densities (10,000 m-2; 20,000 m-2; 30,000 m-2; and 40,000 m-2) were tested to determine growth (number of chaetigerous segments) and survival after 7 days in nursery cups. Results showed that the number of segments of early juveniles did not vary significantly (p>0.05) in all treatments. Final number of survivors were higher (p<0.05) at 40,000 m-2 (33,700 =/ 1,488 ind) than 10,000m-2 (8,300 =/ 1.097 ind) 20,000 m-2 (16,100 =/ 1,095 ind.) and 30,000 m-2 (26,800 =/ 1,489 ind.). This suggests that Marhysa sp. Juveniles can be produced in high numbers despite high stocking densities using the current nursery protocols. The outdoor grow -out experiment was conducted in a brackishwater pong where early juveniles were stocked at four densities. (500 m-2 ; 1,000 m-2 ; 1,500 m-2; and 2,000 ind.m-2) at two culture periods (3 and 4 months) to determine of 500 ind.m-2 resulted in bigger (P<0.05) polychaetes but total length, survival rate, and biomass were not different (P>0.05) from those in higher stocking densities. Survival rates of the polychaetes did not differ significantly (P>0.05) between 4 months (18.1 =/ 12..1%) and 3 months (16.1 =/ 9.2%after 4 months of culture compared to just 3 months , suggesting longer culture periods can improve overall yields. The organic matter in sediments decreased from 5% to 4% both treatments for stocking densities and culture periods indicating the potential of Marphysa sp as a bioremediation agent.